Response to Treatment in a Prospective Cohort of Patients with Large Ulcerated Lesions Suspected to Be Buruli Ulcer (Mycobacterium ulcerans Disease) - Kibadi, Kapay; Boelaert, Marleen; Fraga, Alexandra G.; Kayinua, Makanzu; Longatto-Filho, Adhemar [UNESP]; Minuku, Jean-Bedel; Mputu-Yamba, Jean-Baptiste; Muyembe-Tamfum, Jean-Jacques; Pedrosa, Jorge; Roux, Jean-Jacques; Meyers, Wayne M.; Portaels, Francoise (Public Library Science, 2010)
Background: The World Health Organization (WHO) advises treatment of Mycobacterium ulcerans disease, also called Buruli ulcer'' (BU), with a combination of the antibiotics rifampicin and streptomycin (R+S), whether followed by surgery or not. In endemic areas, a clinical case definition is recommended. We evaluated the effectiveness of this strategy in a series of patients with large ulcers of >= 10 cm in longest diameter in a rural health zone of the Democratic Republic of Congo (DRC).Methods: A cohort of 92 patients with large ulcerated lesions suspected to be BU was enrolled between October 2006 and September 2007 and treated according to WHO recommendations. The following microbiologic data were obtained: Ziehl-Neelsen (ZN) stained smear, culture and PCR. Histopathology was performed on a sub-sample. Directly observed treatment with R+S was administered daily for 12 weeks and surgery was performed after 4 weeks. Patients were followed up for two years after treatment.Findings: Out of 92 treated patients, 61 tested positive for M. ulcerans by PCR. PCR negative patients had better clinical improvement than PCR positive patients after 4 weeks of antibiotics (54.8% versus 14.8%). For PCR positive patients, the outcome after 4 weeks of antibiotic treatment was related to the ZN positivity at the start. Deterioration of the ulcers was observed in 87.8% (36/41) of the ZN positive and in 12.2% (5/41) of the ZN negative patients. Deterioration due to paradoxical reaction seemed unlikely. After surgery and an additional 8 weeks of antibiotics, 98.4% of PCR positive patients and 83.3% of PCR negative patients were considered cured. The overall recurrence rate was very low (1.1%).Interpretation: Positive predictive value of the WHO clinical case definition was low. Low relapse rate confirms the efficacy of antibiotics. However, the need for and the best time for surgery for large Buruli ulcers requires clarification. We recommend confirmation by ZN stain at the rural health centers, since surgical intervention without delay may be necessary on the ZN positive cases to avoid progression of the disease. PCR negative patients were most likely not BU cases. Correct diagnosis and specific management of these non-BU ulcers cases are urgently needed.